Study Effecting of Hetero Chitosan Mineralization on Structure of Proteus spp - Walla Shaker Mahmoud (Indian Journal of Forensic Medicine & Toxicology, 2022)
DE protection, demineralization, de colorization, and DE acetylation. Protein accesses were used to obtain chitosan from shrimp shell waste. Using FTIR, SEM and XRD. It was characterized. Also analyzed were the physiochemical parameter such as moisture content, hydrogen meter, viscosity, degree of DE acetylation and solubility The age of bacterial culture influenced its susceptibility to chitosan with cells being most prone to chitosan in the late exponential period. Hetero chitosan oligosaccharides were made up of partially DE acetylated chitosan’s 90%, 75%, and 50% DE acetylated chitosan’s. It was clear that in the presence of the hetero chitosan and their oligosaccharides, the growth of gram –negative bacteria is less inhibited than gram positive bacteria. These results revealed that hetero chitosan’s and their oligosaccharide rely on the antibacterial effects degree of DE acetylation, and molecular weight.